A Novel Autoantibody Induced by Bacterial Biofilm Conserved Components Aggravates Lupus Nephritis - Fu, Wenyan; Liu, Yu; Liu, Fangjie; Liu, Chenghua; Li, Jingjing; Niu, Jiali; Han, Peng; Xu, Dan; Hou, Jiaojiao; Ma, Yuanfang; Feng, Jiannan; Li, Zhanguo; et al. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with multiple autoantibody production and often affects the kidneys, known as lupus nephritis. However, the mechanism underlying lupus nephritis development is unclear. Biofilms that protect bacteria from stress are ubiquitous in almost every environment. Here, we identified that a conserved peptide (HU1) derived from DNABII proteins, one of major bacterial biofilm components, was specifically recognized by sera from about 47% patients with SLE. Moreover, the serum anti-HU1 levels showed a significant positive correlation with lupus nephritis occurrence. Presence of antibodies against HU1 in pristane-induced mice aggravated lupus nephritis, although these antibodies also attenuated bacterial biofilm formation. We further identified that antibodies against HU1 cross-recognized protein disulfide isomerase (P4HB) located on the renal cell surface and inhibited the activities of this enzyme. Our findings reveal a novel mechanism underlying the development of lupus nephritis triggered by bacterial biofilms.